Analysis of Economic Sector Potential in Nusa Tenggara Barat Province for the 2018-2022 Period - Ima Umniyah; Sahri, Sahri; Titi Yuniarti (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
The purpose of this research is to determine and analyze differences in economic sectors that have basic potential between Lombok Island and Sumbawa Island. This research is descriptive quantitative research. By using the loqation quotient, dynamic loqation quotient, and shift-share analysis methods. The research results show that there are differences in economic sectors that have basic potential between Lombok Island and Sumbawa Island. The results of the LQ show that Lombok Island produces fifteen basic economic sectors, namely the processing industry sector with the highest LQ value of 1.51. Meanwhile, Sumbawa Island shows two basic economic sectors, namely the mining and quarrying sector with the highest LQ value of 1.93. The results of the DLQ analysis on Lombok Island show that sixteen economic sectors produce a base sector, namely the construction sector with the highest DLQ value of 12.24, while Sumbawa Island shows one economic sector that produces a base sector, namely the accommodation and food and drink provision sector with the highest DLQ value of 885. 19. The results of the shift share analysis for Lombok Island show that the total value of sectoral performance makes a significant contribution to the economy of West Nusa Tenggara Province, but has low competitiveness or competitive advantage. Meanwhile, on Sumbawa Island, it shows that the total value of sectoral performance makes a big contribution and has high competitiveness or competitive advantage for the economy of West Nusa Tenggara Province.